Pelatihan Robotik untuk Meningkatkan Pembelajaran Steam di SD Muhammadiyah Beji, Kabupaten Gunung Kidul, Yogyakarta - Arianto, Eko; Siswoyo, Patresius Agus; Noviyanto, Antonius Hendro (Jurnal ETAM, 2024)
The robotics training at SD Muhammadiyah Beji was conducted as an effort to optimize STEAM (Science, Technology, Engineering, Art, and Mathematics) education at the primary school level. This program aims to provide new learning experiences for students through the introduction of robotics and to assist teachers in enhancing their understanding and skills in implementing STEAM concepts. In this program, students are introduced to basic robot programming using block-based languages designed to make programming accessible and engaging. Additionally, the training involves teachers in utilizing robotic devices as innovative and interactive teaching tools. The results of the training show that students were highly enthusiastic and developed a greater interest in science and technology. On the other hand, teachers gained a better understanding of STEAM-based learning and how to integrate it into their curriculum. The program successfully created a model of teaching that can be adopted by other schools and provided a reference for innovative learning methods to boost student interest. It is hoped that this training will inspire students to aspire to become technology experts in the future.